(3bhGWY GdCOdI aj CUhd Gdabgs - (3GdSeYGfj , efUhQ Hf eMeO Hf YHO GdLHGQ Hf CMeO GdJejej,J (B489 (3g` s
(3ChdgG (B:s
(3bGd Gddg JYGdi (B( (3ahdG faQ ef cd aQbg (B) (3CeQ Gddg JYGdi HGdJabg ai GdOjf hGddg JYGdi eaJM Yjf HUjQI ef CMH ef YHGOg s
(3BNQgG (B:s
(3aPdc jchf Ydi GdfGOQ hEPG cGf GdeaYhd aSNkG ai Mb GdeJYGbOjf dGHO Cf jchf aSNkG ai Mb ZjQgeG hJeGe Pdc Hdbi ai NdGajGJ GdaQhY hbO PcQfG CcKQ ef Pdc ai GdeUfa GdPi UfafGg aef CQGO CcKQ eeG bdfGg adjQLY Edjg hGddg GdeYjf Ydi Pdc Hefg haVdg hUs
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B303 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B20s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1357s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
Keywords: (3CUhd Gdabgs